Mathematical Representation Ability in Junior High School Students: Study Literature Review - Minda Ayu Rahma Sari; Dwi Rahmawati; Sutrisni Andayani (Journal of Educational Sciences, 2026)
This study aims to examine junior high school students’ mathematical representation abilities through a literature review of empirical research discussing forms of representation, influencing factors, and the instructional models used to enhance these abilities. The analysis indicates that visual, symbolic, and verbal representations remain the primary components explored in mathematics learning, with many students still struggling to connect these forms effectively. Prior studies suggest that such difficulties are influenced by learning styles, prior knowledge, and limited exposure to non-routine problem-solving tasks. Various instructional models, such as Realistic Mathematics Education, Contextual Teaching and Learning, problem-based learning, discovery learning, and technology-supported media including GeoGebra and mathematics comics, have shown positive effects on improving representational performance. The literature also emphasizes the importance of teacher scaffolding and contextually relevant learning materials in strengthening students’ representational understanding. Overall, this review highlights that mathematical representation ability is a crucial foundation in junior high school mathematics. The development of instructional strategies that encourage exploration and meaningful connections across representation forms must be further strengthened. Future research is encouraged to adopt mixed-methods approaches to provide a more comprehensive understanding of students’ representational processes.